Natural regeneration and seed production of pine stands on the dumps of coal mining industry in Kuzbass - V. I. Ufimtsev (Сибирский лесной журнал, 2016)
On the basis of the accounting of undergrowth in 5 gradations of crown closure density of Scots pine (Pinus sylvest-ris L.) stands, growing on the dumps in 4 ecological-geographic areas of Kuzbass, inverse relation of parameters of renewal from hydrothermal coefficient of the district is established. Optimum conditions develop in a steppe kernel where the number of shoots, seed production and undergrowth reaches 110 thousand trees per hectare with crown closure of 50 % and density of forest stand of 0.75 thousand trees of the II class of age on 1 hectare. At decrease or increase of forest canopy density of the main tree stand layer quantitative characteristics decrease. The smallest amount of undergrowth is recorded in the mountain-taiga area – from 0.4 to 23 thousand trees per hectare with a tendency to increase in the process of increasing crown closure. Areas of the northern forest-steppe and the southern forest-steppe on quantitative signs of renewal are intermediate. The number of undergrowth has high direct correlation dependence on the size of the current fructification of forest stands – around a steppe kernel ripens to 3.7 million seeds on 1 hectare, in mountain and taiga – to 0.39 million seeds on 1 hectare. Sowing qualities of seeds – the weight 1000, energy of germination and viability, and morphometric characteristics of 2-year seedlings, which are grown up from them – height, diameter and point of a vital state between ecological-geographic areas have no statistically reliable distinctions, but the characteristics stated above, than in the stands on zone soils. It testifies to usefulness of dumps’ conditions for natural regeneration of Scots pine, high actual reproductive opportunities for pine stands in forest-steppe areas and a steppe kernel, and also potential opportunities of the stands in the mountain and taiga region of the southern Kuzbass.